Effectiveness of supervisors' expertise, professionalism, and Islamic work ethics on postgraduate thesis supervision at international tertiary institution. - Salleh, Mohamad Johdi; Atan, Ayunita (Pusat Pengembangan Integrasi Ilmu Naqli & Aqli (PIINA), 2017)
The study aims to examine the effectiveness of postgraduate thesis supervisions on Supervisors’ Expertise, Professional Development, and, Islamic Work Ethics at International Islamic Tertiary Institution. The principles and dimensions of postgraduate thesis supervision have been assessed by using models adapted from Aspland & O’Leary (1999) and IIUM Code of Ethics (2016). The study employed a purposive sampling of 163 postgraduate students who were actively involved in research activities of Masters and PhD degrees at the Faculty/Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia (IIUM), Kuala Lumpur. KIRKHS has the highest number of postgraduate students nationally and internationally among fourteen faculties at IIUM. The questionnaires have been tested for reliability and validity comprised three main dimensions of 15 items and evaluated in 5-Likert responses. The data collected were analyzed by using SPSS Version 20 and presented in frequency, percentage, mean and standard deviation. The findings of the study indicated, the students perceived the most effective practice were Islamic Work Ethics achieved mean 4.19 and standard deviation 0.812, followed by Supervisors’ Expertise acquired mean 4.09 and standard deviation 0.861, and, Professionalism Development with mean 3.55 and standard deviation 1.025. It is hoped that findings of the study may be used as an appropriate guide for supervisions of postgraduate students at tertiary institutions in Malaysia and world-wide with true success and enlightening prosperity in the era of globalization.